Multichannel radiometer calibration: A new approach - Diaz, Susana Beatriz (2005)
The error in irradiance measured with Sun-calibrated multichannel radiometers may be large when the solar zenith angle (SZA) increases. This could be particularly detrimental in radiometers installed at mid and high latitudes, where SZAs at noon are larger than 50° during part of the year. When a multi-regressive methodology, including the total ozone column and SZA, was applied in the calculation of the calibration constant, an important improvement was observed. By combining two different equations, an improvement was obtained at almost all the SZAs in the calibration. An independent test that compared the irradiance of a multichannel instrument and a spectroradiometer installed in Ushuaia, Argentina, was used to confirm the results.